Breaking out of the Expat Bubble How to Make Intercultural Connections and Friends - van Bakel, Marian (Taylor & Francis, 2024)
Moving abroad means having to settle into a new host country. This book enables expats and those who support them to create intercultural connections and friendships both within and outside the workplace. Having left behind a large part of their social network, expats need to make local friends to really settle in. This book shows you how this works, and that breaking out of the expat bubble and making local friends helps you adjust and settle in the new place you call home. Organisations and societies should also support expats if they would like to retain this international talent. It is important to create the conditions for expats to build a social network, for example by connecting them with a local buddy. Learn more in this book about the advantages of such contact and how to set up and manage a buddy system to the benefit of both your expats and your organisation or community. The book is illustrated by many quotes from almost 20 years of research and features 11 real-world experiences of expats around the world. It also includes practical recommendations for expats, organisations and societies. An invaluable resource on creating more intercultural connections and friendships in the workplace and the local community, this book will be well placed in the hand luggage of expats - especially those who go without much organisational support - as well as on the desks of managers and HR professionals who would like to better support expats on this great adventure.